Human health and forests: a global overview of issues, practice and policy - Colfer, C.J.P. (Earthscan, 2008)
This book is the first comprehensive introduction to the issues surrounding the health of people living in and around forests, particularly in Asia, South America and Africa. Part I is a set of synthesis chapters, addressing policy, public health, environmental conservation, and ecological perspectives on health and forests including women and child health, medicinal plants and viral diseases such as Ebola, SARS and Nipah Encephalitis. Part II takes a multi-lens approach to lead the reader to a more concrete and holistic understanding using case studies from around the world that cover issues as important as the links between HIV/AIDs and the forest sector and diet and health. Part III looks at the specific challenges to health care delivery in forested areas including remoteness and the integration of traditional medicine with modern health care. Generous use of boxes with specific examples add layers of depth to the analyses and the book concludes with a synthesis designed for use by practitioners and policymakers to work with forest dwellers to improve their health and their ecosystems. This book a vital addition to the knowledge base of all professionals, academics and students working on forests, natural resources management, health and development world-wide.